2006
DOI: 10.1007/s00601-006-0165-z
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Boson System at Next-to-Next-to-Leading Order

Abstract: We discuss effective field theory treatments of the problem of three particles interacting via short-range forces (range R ≪ a 2 , with a 2 the two-body scattering length). We show that forming a once-subtracted scattering equation yields a scattering amplitude whose low-momentum part is renormalization-group invariant up to corrections of O(R 3 /a 3 2 ). Since corrections of O(R/a 2 ) and O(R 2 /a 2 2 ) can be straightforwardly included in the integral equation's kernel, a unique solution for 1+2 scattering p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(117 citation statements)
references
References 43 publications
6
110
1
Order By: Relevance
“…A formalism which employs a partial resummation of range effects was developed in Refs. [9,10,11] and observables were calculated up to nextto-next-to-leading order (N2LO) in the l/a expansion. Hyperradial coordinates and the Wilsonian renormalization group were used to re-derive the leading-order amplitude and develop a power counting for sub-leading effects in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A formalism which employs a partial resummation of range effects was developed in Refs. [9,10,11] and observables were calculated up to nextto-next-to-leading order (N2LO) in the l/a expansion. Hyperradial coordinates and the Wilsonian renormalization group were used to re-derive the leading-order amplitude and develop a power counting for sub-leading effects in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The calculations of [40] were based on the adiabatic hyperspherical expansion in three-body configuration space, while the hard-core version of the twodimensional Faddeev differential equations has been used in [33]. References [41,42,43,44,45,46,47,48] suggest that the 4 He 3 ground state itself may be considered as an Efimov state since, given the 4 He- 4 He atom-atom scattering length, both the 4 He 3 ground-state and excited-state energies lye on the same universal scaling curve (for details, see, e.g., [49,Sections 6.7 and 6.8]). …”
mentioning
confidence: 99%
“…[28,29] showed that if the cutoff is taken to infinity in Eq. (10) with t 2B 0 replaced by t 2B 0 + t 2B 1 + t 2B 2 , then a second three-body datum is not needed for renormalization.…”
Section: Some Results At Nnlomentioning
confidence: 99%